THE NEW YEAR 2018 OF THE WOMAN. - WEXLER, ELLEN (Moment Magazine)
The article presents the Jewish women vying to run for major political positions in 2018. Among these women candidates are Kathy Manning and Susan Turnbull. Those who have been elected to major political office in the U.S. are also presented including Florence Prag Khan, Elizabeth Holtzman, and Gladys Spellman.